PEMANFAATAN SOFTWARE KOMPUTER UNTUK MENINGKATKAN KECERDASAN EMOSI (EQ) ANAK - Hardianto, Deni (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The emergence of computer software into education and learningsector has to be understood seriously by teachers, parents andeducational staff, including stakeholders. Using the computersoftware improperly basically could give some bad impacts forstudents’ development. On the other hands, computer has acapability to bring such positive impacts for the students’ growth andknowledge. Therefore, teachers, parents and instructionaldevelopment must pay a serious attention to some aspects that couldharm students. The excellent understanding about computerutilization effectively will decrease the negative risk of computersoftware utilization. By designing and developing computer softwareusing the students’ instructional and psychological principles willimprove the understanding, promote intellectual intelligence andeven emotional intelligence (EQ) for students. Computer softwarecould improve and develop values, help solving the problems, teachstudents to be a multiple thinker and solve the problems by findingnew perspectives.